2015
DOI: 10.1007/s00792-015-0731-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of 2-keto-3-deoxy-l-rhamnonate dehydrogenase belonging to the MDR superfamily from the thermoacidophilic bacterium Sulfobacillus thermosulfidooxidans: implications to l-rhamnose metabolism in archaea

Abstract: We identified the non-phosphorylated L-rhamnose metabolic pathway (Rha_NMP) genes that are homologous to those in the thermoacidophilic archaeon Thermoplasma acidophilum in the genome of the thermoacidophilic bacterium Sulfobacillus thermosulfidooxidans. However, unlike previously known 2-keto-3-deoxy-L-rhamnonate (L-KDR) dehydrogenase (KDRDH) which belongs to the short chain dehydrogenase/reductase superfamily, the putative KDRDHs in S. thermosulfidooxidans (Sulth_3557) and T. acidophilum (Ta0749) belong to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…LRA5 (KDRDH) was identified as an NAD+ specific enzyme belonging to the short-chain dehydrogenase/reductase (SDR) superfamily [ 11 ] and has been shown to convert L-KDR to 2, 4-diketo-3-deoxy-L-rhamnonate. Interestingly, another KDRDH belonging to the medium chain dehydrogenase reductase (MDR) superfamily has been biochemically characterized in Sulfobacillus thermosulfidooxidans and was found to catalyze the same metabolic reaction [ 10 ]. We analysed and compared the PFAM domains in the protein sequences of LRA5 of both species.…”
Section: Discussionmentioning
confidence: 99%
“…LRA5 (KDRDH) was identified as an NAD+ specific enzyme belonging to the short-chain dehydrogenase/reductase (SDR) superfamily [ 11 ] and has been shown to convert L-KDR to 2, 4-diketo-3-deoxy-L-rhamnonate. Interestingly, another KDRDH belonging to the medium chain dehydrogenase reductase (MDR) superfamily has been biochemically characterized in Sulfobacillus thermosulfidooxidans and was found to catalyze the same metabolic reaction [ 10 ]. We analysed and compared the PFAM domains in the protein sequences of LRA5 of both species.…”
Section: Discussionmentioning
confidence: 99%
“…Via formation of 2-keto-3-deoxy-L-fuconate (KDF) this sugar acid is further oxidized to 2,4-diketo-3-deoxy-Lfuconate, which is finally cleaved to pyruvate and lactate. Recent studies revealed the existence of a closely related route for degradation of L-rhamnose in the thermoacidophilic bacterium Sulfobacillus thermosulfidooxidans (Bae et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the predicted l ‐rhamnono‐lactonases from S. thermosulfidooxidans and T. acidophilum belong to the metallo‐hydrolase‐like MBL fold superfamily (Supplementary Fig. ) (Bae et al , ). It should be noted that the only characterized sugar lactonase in archaea is the H. volcanii pentonolactonase, which is a member of the SMP‐30/gluconolactonase/LRE‐like protein family (Sutter et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Beside in haloarchaea, we also identified lut genes in the diketo‐hydrolase gene cluster of Sphingomonas sp. and S. thermosulfidooxidans (Watanabe and Makino, ; Bae et al , ) suggesting that Lud‐containing proteins have a similar function in l ‐rhamnose degradation in these bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation